2004
DOI: 10.1016/j.jacc.2003.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary results of mitral valve repair for infective endocarditis

Abstract: Mitral valve repair is frequently feasible and gives good results in patients with infective endocarditis. Patients operated on for acute endocarditis experience more events during follow-up than those operated on after healed endocarditis but have excellent late survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(48 citation statements)
references
References 27 publications
0
47
0
1
Order By: Relevance
“…Repair in active endocarditis was associated with a higher rate of major adverse cardiac events but had equivalent survival to those with fully treated endocarditis. (19) Only 30% of our patients with mitral endocarditis were amenable for repair and they had no valve related mortality but 33% had major adverse cardiac events.…”
Section: Infective Endocarditismentioning
confidence: 84%
“…Repair in active endocarditis was associated with a higher rate of major adverse cardiac events but had equivalent survival to those with fully treated endocarditis. (19) Only 30% of our patients with mitral endocarditis were amenable for repair and they had no valve related mortality but 33% had major adverse cardiac events.…”
Section: Infective Endocarditismentioning
confidence: 84%
“…Mitral valve repair is associated with lower perioperative morbidity and mortality, better preservation of left ventricular function, avoidance of long-term anticoagulation and the associated risks of bleeding, a low rate of thromboembolic complications, a low risk of infective endocarditis, excellent freedom from reoperation, and improved long-term survival. [11][12][13] Although individual centers with an interest in mitral valve surgery have demonstrated high repair rates, the majority of patients having mitral valve surgery in North America continue to receive a replacement rather than a repair. 14 We observed a dramatic effect of hospital procedural volume on mitral valve repair rates, with repair rates climbing from 47.7% in the lowest-volume quartile to 77.4% in the highest-volume quartile.…”
Section: Circulation February 20 2007mentioning
confidence: 99%
“…For example, Iung et al demonstrated that mitral valve repair was feasible in 81% of patients with IE and resulted in an early mortality of 3.2% and a 7-year event-free survival of 78%, 1 Podesser et al reported that actuarial survival at 5 years was 87±12.7%, 2 and both Muehrcke et al 3 and Sternik et al 4 demonstrated that early and late mortality and event-free survival were better in patients undergoing mitral valve repair compared with replacement for acute endocarditis. Although comparison of patients undergoing valve repair and replacement is difficult because of the variation in the clinical condition of the patients at the time of surgery, mitral valve repair still remains an attractive procedure because of better preservation of left ventricular function and a lower incidence of valve-related events.…”
Section: Discussionmentioning
confidence: 99%